One‐ and Two‐Electron Transfer Oxidation of 1, 4‐Disilabenzene with Formation of Stable Radical Cations and Dications. Issue 5 (16th December 2021) - Chen, Yilin; Chen, Zhikang; Jiang, Liuyin; Li, Jiancheng; Zhao, Yiling; Zhu, Hongping; Roesky, Herbert W.
Abstract: Electron‐transferable oxidants such as B(C6 F5 )3 / n BuLi, B(C6 F5 )3 /LiB(C6 F5 )4, B(C6 F5 )3 /LiHBEt3, Al(C6 F5 )3 /( o ‐RC6 H4 )AlH2 (R=N(CMe2 CH2 )2 CH2 ), B(C6 F5 )3 /AlEt3, Al(C6 F5 )3, Al(C6 F5 )3 / n BuLi, Al(C6 F5 )3 /AlMe3, (CuC6 F5 )4, and Ag2 SO4, respectively were employed for reactions with (L)2 Si2 C4 (SiMe3 )2 (C2 SiMe3 )2 (L=PhC(N t Bu)2, 1 ). The stable radical cation [1 ] +. was formed and paired with the anions [ n BuB(C6 F5 )3 ] − (in 2 ), [B(C6 F5 )4 ] − (in 3 ), [HB(C6 F5 )3 ] − (in 4 ), [EtB(C6 F5 )3 ] − (in 5 ), [(C6 F5 )3 Al]2 ( μ ‐F)] − (in 6 ), [ n BuAl(C6 F5 )3 ] − (in 7 ), and [Cu(C6 F5 )2 ] − (in 8 ), respectively. The stable dication [1 ] 2+ was also generated with the anions [EtB(C6 F5 )3 ] − (9 ) and [MeAl(C6 F5 )3 ] − (10 ), respectively. In addition, the neutral compound [(L)2 Si2 C4 (SiMe3 )2 (C2 SiMe3 )2 ][ μ ‐O2 S(O)2 ] (11 ) was obtained. Compounds 2 –11 are characterized by UV‐vis absorption spectroscopy, X‐ray crystallography, and elemental analysis. Compounds 2 –8 are analyzed by EPR spectroscopy and compounds 9 –11 by NMR spectroscopy. The structure features are discussed on the central Si2 C4 ‐rings of 1, [1 ] +., [1 ] 2+, and 11, respectively. Abstract : Compounds [1] +. [R] − and [1 ] 2+ ⋅ 2[R] − have been prepared from the respective one‐ and two‐electron transfer reactions of 1, 4‐disilabenzene (L)2 Si2 C4 (SiMe3 )2 (C2 SiMe3 )2 (1 ) by using the transferable organometallic oxidants and characterization by X‐ray crystallography.,